The effects of coping strategies and relaxation exercises on anxiety, hopelessness, life satisfaction, and well-beıng in the elderly people with diabetes: An experimental study (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the effects of coping strategies and relaxation exercises on anxiety, hopelessness, life satisfaction, and well-being in elderly people with diabetes.Materials and Methods: A total of 30 participants were randomly assigned to three experimental conditions. In the first condition, the participants were informed about diabetes as well as how to cope with it. In the second condition, the participants were provided with breathing and relaxation exercises, which were accompanied by relaxing music, in addition to informing about diabetes and coping strategies. The control group was only informed about diabetes. The data were analyzed by ANOVA with 3 x 2 last factors repetitive.Results: There was no difference between the conditions in terms of state anxiety, hopelessness and life satisfaction scores (p>0.05), but the difference after the intervention was significant (p0.05). According to the Scheffe test, a) status anxiety score was determined between the first condition and the control group; b) life satisfaction score was significantly different between the first condition and second condition and between the second condition and control group. Significant differences were also found between pre-and post-intervention concerning anxiety, hopelessness and life satisfaction scores. Conclusions: Findings suggest that explaining the methods of coping with diabetes can decrease the level of state anxiety, and the addition of breathing and relaxation exercises can enhance life satisfaction.
Keywords: Anxiety; elderly with diabetes; hopelessness; life satisfaction; well-being